Field Implementation of a Local Wisdom-Based Practicum Module for Character Education in Early Childhood Learnin - Putri Cahya Oktaviyana; Fajar Luqman Tri Ariyanto; Dwi Bagus Rendy Astid Putera; Alvira Eka Rahel Guivara; Inggrid Anggraeny; Chelci Dianasari; Zein Nizam (Journal of Comunity Service in Early Childhood Education, 2025)
Background: The integration of character education, particularly environmental stewardship, in early childhood education is often constrained by conventional teaching approaches that limit experiential learning opportunities. Aims: This community service program aims to implement a local wisdom-based practicum module to enhance environmental character development in early childhood learning. Methods: This community service program employed the Participatory Action Research (PAR) approach, involving collaborative processes between researchers and teachers through four stages: planning, action, observation, and reflection. The program began with a needs analysis and joint module design, followed by implementation through hands-on activities, while data were collected through observation and interviews and analyzed descriptively to evaluate program effectiveness. Result: The community service results indicate a significant increase in children’s engagement and enthusiasm in practice-based learning, along with the development of pro-social and environmental behaviors such as cooperation, cleanliness awareness, and scientific curiosity. In addition, teachers’ capacity as partners improved in understanding and implementing the local wisdom-based practicum module. Approximately 90% of participants showed positive responses, and the resulting practicum module was considered practical, applicable, and has potential for sustainable use and replication. Conclusion: The implementation of a local wisdom-based practicum module through a community service program effectively enhances children’s environmental character and supports experiential learning in early childhood education. It also strengthens teachers’ capacity in applying innovative and contextually relevant instructional approaches. Therefore, this program offers a practical, sustainable, and replicable model for integrating character education in early childhood settings.